Evaluación de la contaminación de las aguas del río Yamanigüey - Fernández-Rodríguez, Moraima (2024)
Water is essential for the economy and community welfare, but its quality can be affected by natural and human factors. The present research aimed to analyze water contamination in the Yamanigüey River through contamination indexes such as organic matter, suspended solids, pH and Trophy, given that it is one of the most important rivers in Moa. Twelve samples were collected to initially evaluate their physicochemical and bacteriological properties according to the Cuban Standard (NC 1021, 2014) "Communal hygiene - water supply sources - quality and sanitary protection", the Cuban Standard (NC 827, 2017) "Drinking water - sanitary requirements" and the World Health Organization (WHO, 2011) standard "Guidelines for the quality of water for human consumption", followed by the application of the contamination indexes. As main results it was obtained that, according to the Cuban Standards evaluated and the World Health Organization Standard, the waters are both below and above the maximum and minimum acceptable limits. We concluded that the waters of the Yamanigüey River are classified in waters with medium, low and no degree of contamination according to the evaluated indexes.